PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN VIEW FROM COGNITIVE ASSESSMENT ON MATERIAL REACTION RATE - Annisa Nandiva Wardhana Ritonga (Jurnal Pembelajaran Sains, 2022)
The level of completeness of learning outcomes is influenced by the implementation of the learning process. In the realm of education, learning chemistry is included as a field of study that is difficult to understand. Chemistry contains complex concepts. The rate of reaction is one of the most complex materials. For this reason, a Problem Based Learning learning model is needed. The method used in this paper is using the review method by selecting several articles and journals about improving student learning outcomes on the reaction rate material through the application of the Problem Based Learning learning model. Based on the search results, 22 research journals were obtained which were then exported in ris format using the Mendeley Desktop application and processed using VOSviewer. Based on research data from 3 analyzed journals, it can be seen that the use of Problem Based Learning learning models can improve student learning outcomes on the subject of reaction rates. This is evidenced by the increasing percentage of learning from the 3 schools where the 3 selected articles were researched. In MA Maarif NU 1 Samarinda, it increased by 70%; at SMA Negeri 4 Merauke increased 53%; and at Trisakti Catholic High School it increased by 26%.